Reading the Stars - Williams, Peter (IMF Working Papers; Working Paper, 2020)
Following the global financial crisis, significant uncertainty has existed around the U.S. economy's steady state equilibrium. This paper uses a factor model to provide a new approach to estimating 'the stars' (i.e. the neutral interest rate, maximum employment, and the level and growth rate of potential output) that are most consistent with a medium-term equilibrium where inflation converges to the FOMC's two percent target. It is applicable to any country with an inflation targeting central bank. It also explicitly incorporates estimates of the extensive margin of slack in the labor market, which has proven to be an important factor in describing the post-financial crisis landscape.